Preparation and Characterization of Chitosan–Durian Seed Composite Adsorbent for Tofu Wastewater Treatment - Silvia Devi Eka Putri; Endi Adriansyah; Rifqi Sufra; Nurul Asni; Yuyun Lusini; Anugrah Thoriq; Zidan Ashri Aksaronas; Saskia Eka Dian; M. Syaiful (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
The tofu industry generates wastewater containing high concentrations of total dissolved solids (TDS) and total solids (TS), posing significant environmental concerns. This study aimed to develop a chitosan-modified durian seed (Durio zibethinus) composite bioadsorbent for the removal of TS and TDS from tofu wastewater. The composite was characterized using scanning electron microscopy (SEM), X-ray fluorescence (XRF), and particle size analysis (PSA), followed by batch adsorption experiments at different adsorbent dosages. The initial wastewater contained 7,528 mg/L TDS and 9,139 mg/L TS. The composite exhibited superior adsorption performance compared with pristine chitosan, achieving a maximum TDS removal efficiency of 65.84%, reducing the TDS concentration to 2,572 mg/L, while TS removal reached 47.70%, with the final TS concentration decreasing to 4,780 mg/L at an adsorbent dosage of 1 g. Material characterization demonstrated that chitosan modification improved the composite morphology and physicochemical properties, thereby enhancing its adsorption performance. These findings indicate that the chitosan-modified durian seed composite is an effective, low-cost, and environmentally friendly bioadsorbent for tofu wastewater treatment. Furthermore, the utilization of durian seed waste as a bioadsorbent contributes to agricultural waste valorization and supports circular economy practices. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and Sanitation SDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and Production|SDG 13: Climate ActionSDG 15: Life on Land